Static load test and bearing capacity analysis of broken line pretensioned prestressed concrete I-beam - Peisen Wang; Jiacheng Shi; Chenning Song (PLoS ONE, 2025)
The construction technology of broken line pretensioned method, which is suitable for long-span bridges, can greatly improve the flexural strength of concrete members. To study the mechanical performance and failure mode of broken line pretensioned prestressed concrete I-beam, an I-beam with a span of 30 m was taken as the research object and on-site static load tests were carried out. Based on the ABAQUS finite element software, the numerical simulation was carried out to analyze the mechanical properties and failure behavior of the I-beam under the concentrated load, and the ultimate flexural capacity of the I-beam was studied in combination with the theoretical analysis. In addition, the optimized arrangement of prestressed tendons was analyzed. The results show that in the on-site static load tests, the strain values at the mid-span section and 1/4-span basically show a linear growth trend, and the I-beam is always in the elastic stage during the tests. The numerical simulation results are in general agreement with the test data with regard to strain, displacement, and neutral axis position. When the concentrated load reaches 1910 kN, the prestressed tendons at the bottom of the I-beam enter the yield state. The prestressed tendons play a controlling role in the ultimate bearing capacity of the I-beam. The numerical simulation result of the ultimate bending moment in the mid-span section is 3.55% larger than the theoretical analysis result, and the theoretical calculation formulas tend to be conservative. When the prestressed tendons are arranged by the four-fold point method, the I-beam has higher stiffness and bearing capacity after concrete cracking. The research results can provide a reference for the design and construction of broken line pretensioned prestressed concrete I-beam.